Low concentrations of sodium hypochlorite affect population dynamics in Gyrodactylus salaris (Malmberg, 1957): practical guidelines for the treatment of the Atlantic salmon, Salmo salar L. parasite. Issue 12 (15th January 2014) - Hagen, A G; Hytterød, S; Olstad, K
Abstract Atlantic salmon, Salmo salar L. parr (age 1+), infected by the monogenean ectoparasite Gyrodactylus salaris (Malmberg, 1957), were exposed to chlorine (Cl)‐enriched water at three different concentrations: Cllow (0–5 μg Cl L−1), Clmedium (18 μg Cl L−1) and Clhigh (50 μg Cl L−1). There was a negative correlation between G. salaris infections and the hypochlorite concentrations added. The parasite infection was eliminated by day 6–8 and day 2–4 in the groups Clmedium and Clhigh, respectively, while inhibition of G. salaris population growth was observed in the Cllow group. An important note to this matter, however, is that the G. salaris specimens observed at day 6 in Clmedium and at day 2 in Clhigh were all considered dead by subjective judgement. No mortality in the salmon parr was observed during the first 8 days of the experiment, demonstrating that Cl has a stronger effect on G. salaris than on the salmonid host. The differences in sensitivity between the parasite and the Atlantic salmon indicate that hypochlorite has a potential use as a parasiticide with a therapeutic margin. The low‐dose sensitivity may imply that Cl pollution in urban areas may pose a greater risk towards biodiversity than previously assumed.